KOMPLIKASI PASKA TRANSPLANTASI GINJAL - Juliana, I Made; Sidharta Loekman, Jodi (journal of internal medicine, 2007)
Renal transplantation is the take over of kidney from healthy person and then be transplanted to the other person who hassevere and permanent kidney function disorder. Renal transplantation is the most effective treatment for terminal stage of chronickidney disease. The survival of patients who underwent renal transplantation depend on some factors including screening ofpatients, pretransplantation management, surgery technic and management of patients after renal transplantation. Complicationsafter renal transplantation devide to surgery complications and non surgery (medical) complications. Surgery complications aremayor complication such as bleeding and anaestesion drug effect and the other complications due to transplantation process.Medical complications are rejection (hyperacute, acute and chronic rejection), infection, cardiovascular disease, anemia,hypertension, diabetes mellitus, dislipidemia, hyperhomocysteinemia, malignancy, lymphoproliferative disease and psychologicaleffect. Rejection is the most important complication. If hyperacute rejection ocured, kidney transplant must be take over to avoidmore severe systemic inflammation respon. New generation of humanized IL-2 receptor antibody, daclizumab (zenapax) candecrease the incident of hyperacute rejection. Acute rejection can be treated with steroid, polyclonal antilymphocyte globulin,monoclonal antibody OKT3 and plasma exchange. Chronic rejection was difficult to treat. Immunosupresion agen have no muchrole because destroyed were occured. Prevention just to manage risk factors and then wait the other transplantation. For the othercomplications, the management based on etiology and the type of complication.